Metabolic syndrome markers in wistar rats of different ages - Ghezzi, Ana Carolina [UNESP]; Cambri, Lucieli Teresa [UNESP]; Botezelli, Jose Diego [UNESP]; Ribeiro, Carla [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Rostom de Mello, Maria Alice [UNESP] (Biomed Central Ltd., 2012)
In recent decades, metabolic syndrome has become a public health problem throughout the world. Longitudinal studies in humans have several limitations due to the invasive nature of certain analyses and the size and randomness of the study populations. Thus, animal models that are able to mimic human physiological responses could aid in investigating metabolic disease. Thus, the present study was designed to analyze metabolic syndrome markers in albino Wistar rats (Rattus norvegicus) of different ages. The following parameters were assessed at two (young), four (adult), six (adult), and twelve (mature) months of age: glucose tolerance (glucose tolerance test); insulin sensitivity (insulin tolerance test); fasting serum glucose, triglycerides, total cholesterol, HDL cholestero, and LDL cholesterol concentrations; glucose uptake in isolated soleus muscle; and total lipid concentration in subcutaneous, mesenteric, and retroperitoneal adipose tissue. We found that aging triggered signs of metabolic syndrome in Wistar rats. For example, mature rats showed a significant increase in body weight that was associated. In addition, mature rats showed an increase in the serum concentration of triglycerides, total cholesterol, and LDL cholesterol, which is characteristic of dyslipidemia. There was also an increase in serum glucose compared with the younger groups of animals. Therefore, aging Wistar rats appear to be an interesting model to study the changes related to metabolic syndrome.
Keywords: Metabolic syndrome; Biochemical parameters; Metabolism; Aging; Wistar rats